Development and validation of a novel questionnaire for self-determination of the range of motion of wrist and elbow. Issue 1 (December 2016) - Schnetzke, Marc; Schüler, Svenja; Keil, Holger; Aytac, Sara; Studier-Fischer, Stefan; Grützner, Paul-Alfred; Guehring, Thorsten
Abstract Background The aim of this study was to develop and validate a novel self-administered questionnaire for assessing the patient's own range of motion (ROM) of the wrist and the elbow. Methods In a prospective clinical study from January 2015 to June 2015, 101 consecutive patients were evaluated with a novel, self-administered, diagram-based, wrist motion assessment score (W-MAS) and elbow motion assessment score (E-MAS). The questionnaire was statistically evaluated for test-retest reliability, patient-physician agreement, comparison with healthy population, and influence of covariates (age, gender, affected side and involvement in workers' compensation cases). Results Assessment of patient-physician agreement demonstrated almost perfect agreement (k > 0.80) with regard to six out of eight items. There was substantial agreement with regard to two items: elbow extension (k = 0.76) and pronation (k = 0.75). The assessment of the test-retest reliability revealed at least substantial agreement (k = 0.70). The questionnaire revealed a high discriminative power when comparing the healthy population with the study group (p = 0.007 or lower for every item). Age, gender, affected side and involvement in workers' compensation cases did not in general significantly influence the patient-physician agreement for the questionnaire. Conclusion The W-MAS and E-MAS are valid and reliable self-administered questionnaires that provide a high level of patient-physician agreement for the assessments of wrist and elbow ROM. Level of evidence: Diagnostic study, Level II